Evaluating Case Attrition along the Medico-Legal Case Referral Pathway for Sexual and Domestic Violence Survivors in Kenya: A Secondary Data Analysis - Rockowitz, Sarah (Victims & offenders, 2024)
Case attrition along the medico-legal referral pathway for sexual and domestic violence survivors has drawn attention worldwide. Despite much research about the prevalence of sexual and domestic violence in Kenya, little is known about factors impacting progress through the medico-legal referral pathway. To address this research gap, we analyzed data from the Wangu Kanja Foundation, based in Nairobi, to test which key case characteristics have explanatory power in predicting case progression. We used a sequential logit model to evaluate case progression as a series of distinct choices. Our analysis revealed that age of the survivor was the strongest predictor for all steps of the pathway, and that the presence of forensic evidence was also associated with increased odds of moving through each step. These findings reflect cultural ideas about what legitimizes a case of sexual or domestic violence and can be used to inform policy targeted at strengthening the case referral pathway in Kenya.